Nonlinear stochastic operators to control the consensus problem in multi-agent systems - Abdulghafor, Rawad Abdulkhaleq Abdulmolla; Turaev, Sherzod; Zeki, Akram M. (IIUM Press, International Islamic University Malaysia, 2017)
The scope of this research is DSQO in order to generate models that will be applied for the consensus problem in MAS. The majorization concept, stochastic matrix, doubly stochastic matrix and QSO theory are included in this research to build the DSQO. The previous works have focused on the design of linear and nonlinear consensus for consensus problem in MAS. In this research, a new paradigm of MAS designs where the linear model and the complex nonlinear are replaced by a flexible (nonlinear model) derived and introduced DSQO model. The distinction between the nonlinear systems and the linear systems is that the nonlinear systems are quite difficult to study and design